Structural changes and carbon reduction due to habitat loss in Atlantic Forest - Rigueira, Dary Moreira Gonçalves; Mariano-Neto, Eduardo (Frontiers in Forests and Global Change, 2023)
Habitat loss is a significant threat to biodiversity in tropical forests, leading to changes in composition, structure, and function. In this study, we aimed to evaluate the influence of the forest amount at the landscape scale on the structure and the stored carbon of tree communities. Eleven landscape samples of 36 km2 (6 × 6 km), with different amounts of forest cover at the landscape scale (between 5 and 60%), were randomly selected within a wide latitudinal range of Atlantic Forests in Brazil. We also used a sample design to control and avoid some biases in landscape-scale studies during the landscape selection, such as the rescue effect from the surrounding landscapes, differences in matrix permeability in each landscape, and the control for the same vegetation type or successional stage. In each selected landscape, we surveyed all woody individuals with a diameter at breast height (DBH) ≥ 2.5 cm in eight plots of 250 m2, randomly placed in the landscape’s forested areas. The structural variables evaluated were: total abundance, the abundance of prominent families, the abundance of large trees (DBH ≥ 30 cm), mean DBH, and average height, besides carbon storage. From the set of 8,179 individuals, we observed a positive correlation between forest amount and the total abundance, the abundance of large trees, and carbon stock. The abundance of the prominent hardwood tree families were positively correlated with forest amount. When comparing the two landscapes with the lowest proportion of habitats (5–15%) and the highest proportion (55−60%), almost one thousand trees and more than 150 T of carbon per hectare are lost. This reduction in the overall abundance and carbon indicates no compensatory effects on the tree community due to a turnover in composition or substitution of large trees for smaller ones. The Atlantic Forest is undergoing a process of homogenization and functional collapse, derived directly or indirectly from habitat loss, leading to a possible regime shift.